ORGANIZATIONAL AND THEORETICAL-LEGAL BASES OF THE PARTICIPATION OF THE SENATE OF THE OLIY MAJLIS OF THE REPUBLIC OF UZBEKISTAN IN THE PROCESS OF ENSURING NATIONAL SECURITY (Scientific journal of the Fergana State University, 2023)
The article provides an understanding of the role of senate committees, the mechanism of preparation of drafts of senate decisions and other regulatory documents. It was noted that the committee on defense and security issues is the main structure of the Senate, which carries out the preliminary review of laws related to the field of defense and security received from the Legislative Chamber and the submission of relevant proposals to the Senate Council. Methods of cooperation with state power and management, economic management bodies, other organizations and institutions, non-governmental non-profit organizations, mass media and citizens were analyzed in connection with issues related to the activities of the committee.